2006
DOI: 10.1093/nar/gkl009
|View full text |Cite
|
Sign up to set email alerts
|

Structural insight into gene transcriptional regulation and effector binding by the Lrp/AsnC family

Abstract: The Lrp/AsnC family of transcriptional regulatory proteins is found in both archaea and bacteria. Members of the family influence cellular metabolism in both a global (Lrp) and specific (AsnC) manner, often in response to exogenous amino acid effectors. In the present study we have determined both the first bacterial and the highest resolution structures for members of the family. Escherichia coli AsnC is a specific gene regulator whose activity is triggered by asparagine binding. Bacillus subtilis LrpC is a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
114
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(121 citation statements)
references
References 52 publications
7
114
0
Order By: Relevance
“…DM1 (Leonard et al, 2001;Koike et al, 2003;Thaw et al, 2006) revealed that the four dimers are arranged as a disc. In the structure of the Pyrococcus sp.…”
Section: Crystallization Data Processing and Structurementioning
confidence: 99%
See 3 more Smart Citations
“…DM1 (Leonard et al, 2001;Koike et al, 2003;Thaw et al, 2006) revealed that the four dimers are arranged as a disc. In the structure of the Pyrococcus sp.…”
Section: Crystallization Data Processing and Structurementioning
confidence: 99%
“…FL11, E. coli AsnC and Bacillus subtilis LrpC, have been determined (Leonard et al, 2001;Koike et al, 2004: Thaw et al, 2006. The proteins consist of an N-terminal helix-turn-helix DNA-binding domain connected by a hinge to the C-terminal RAM (regulation of amino-acid metabolism) domain, with a fold.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Crystal structures have been reported for FFRPs from Pyrococcus sp. OT3, Bacillus subtilis, Escherichia coli, Neisseria meningitides, M. tuberculosis and Sulfolobus tokodaii (Leonard et al, 2001;Koike et al, 2004;Thaw et al, 2006;Ren et al, 2007;Shrivastava & Ramachandran, 2007;Shrivastava et al, 2009;Nakano et al, 2007).…”
Section: Introductionmentioning
confidence: 99%